KOLESTASIS EKTRAHEPATIK ET CAUSA ATRESIA BILIER PADA SEORANG BAYI - Mawardi, Merry; Warouw, Sarah M.; Salendu, Praevilia M. (UNIVERSITAS SAM RATULANGI, 2011)
Abstract: Cholestasis in babies is an obstruction of the flow of bile and other materials excreted by liver, resulting in an increase of direct bilirubin and an accumulation of bile salts. This condition is found in 1:25,000 of live births. One of the causes of cholestasis is biliar atresia that can occur in every part of the extrahepatic bile ducts. In this condition, an inflammatory necrosis destroys the extrahepatic bile duct and ends with an obliteration of the duct. The main causes reported were an immunological process, viral infections (mostly retrovirus type 3), toxic bile acids, and genetic disorders. Biliar atresia is found in 1:15,000 births. Diagnosis of biliar atresia is based on abdominal ultrasonography (USG) to eliminate a choledochus cyst as the cause of obstruction. A liver biopsy has to be carried out to find out the possibility of intrahepatic cholestasis. If the diagnosis of biliar atresia is still difficult to be confirmed, a cholangiography has to be performed. Management of extrahepatic biliar atresia is a surgical intervention of the extrahepatic bile duct (Kasai portoenterostomy technique) and/or a liver transplant. Key words: cholestasis, biliar atresia, complications, management. Abstrak: Kolestasis pada bayi adalah hambatan aliran empedu dan bahan-bahan yang harus diekskresikan oleh hati, yang menghasilkan terjadinya peningkatan bilirubin direk dan penumpukan garam empedu. Kolestatis pada bayi terjadi pada 1:25.000 kelahiran hidup. Atresia bilier dapat terjadi pada semua bagian saluran empedu ekstrahepatik dan merupakan kelainan nekrosis inflamatorik yang menyebabkan kerusakan dan akhirnya obliterasi saluran empedu ekstrahepatik. Penyebab utama yang pernah dilaporkan adalah proses imunologis, infeksi virus terutama , Reo virus tipe 3, asam empedu yang toksik, kelainan genetik. Atresia bilier ditemukan pada 1 dari 15.000 kelahiran. Diagnosis dari atresia bilier ditegakkan berdasarkan pemeriksaan ultrasonografi (USG) abdomen untuk menyingkirkan adanya kista koledokus sebagai penyebab obstruksi. Biopsi hati merupakan pemeriksaan yang penting dilakukan untuk membedakan dengan intrahepatik kolestasis. Jika diagnosis dari atresia bilier tidak bisa ditegakkan dengan pemeriksaan biopsi hati maka pemeriksaan cholangiography sebaiknya dilakukan. Penanggulangan atresia bilier ekstrahepatik terutama dengan pembedahan saluran empedu ekstrahepatik yaitu portoenterostomi teknik Kasai, dan transplantasi hati. Kata Kunci: kolestasis, atresia bilier, komplikasi, penanganan.